Molecular Bases of Endometriosis The Integration Between Research and Clinical Practice - Aparecida Gonçalves, Giovana (IntechOpen, 2019)
What are the objectives of the genetic study of individuals? There is great interest from the medical community and also much concern from the lay press about the potential benefits and harms of genetic screening, gene therapy, and even the possibility of cloning individuals. The current use of genetic tests for the detection and treatment of endometriosis is still at an early stage but very important. The determination of susceptibility markers will be increasingly explored in clinical studies and their uses will be much more defined. Still, it seems increasingly likely that major changes will occur over the next decade in how we evaluate and treat our patients. In particular, surgeons and clinicians will have the opportunity to use a number of new tests to predict the future appearance of endometriosis in patients still free of the disease. They may have the power to explore the best therapeutic modality for a particular patient according to his/her genetic makeup. And they will be able to more specifically target prevention measures for family members of people already affected by the disease. It should be understood that molecular diagnosis, especially in asymptomatic individuals, does not mean disease but an increased risk of developing a disease. Ethical implications exist and should not be underestimated. Patients should be advised about the likely implications of such tests, not only after but especially before the achievement of these. A major step has already been overcome and we currently have the basic tools for a new leap in understanding human pathologies responsible for much of the world's mortality. Bridging the great barrier that still separates this basic knowledge and clinical practice is quite a significant challenge.